2018
DOI: 10.1088/2057-1976/aad0d0
|View full text |Cite
|
Sign up to set email alerts
|

Application of the ActiGraph GT9X IMU for the assessment of turning during walking and running

Abstract: Objective. The primary purpose of this study was to examine the use of the ActiGraph GT9X gyroscope and magnetometer for turn detection and quantifying turn degree during walking and running. The secondary purpose was to examine the effect of varying turn degrees during walking and running on oxygen consumption. Approach. Participants (N=17) completed pivot trials, straight-line treadmill walking and running (3-6 mph) and four turn conditions (45°, 90°, 135°, and 180°) during overground walking and running. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…54,55,59,81 19 studies included a combination of two or more COD angles ranging from 45 to 360 . 35,37,39,48,50,52,56,[61][62][63][64][65][78][79][80]84,85,90 Quality assessment. The quality assessment results for all validity/reliability studies is presented in Appendix 3.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…54,55,59,81 19 studies included a combination of two or more COD angles ranging from 45 to 360 . 35,37,39,48,50,52,56,[61][62][63][64][65][78][79][80]84,85,90 Quality assessment. The quality assessment results for all validity/reliability studies is presented in Appendix 3.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…49 In 10 studies, the age of participants was not reported. 38,51,52,[84][85][86][87][88][89][90] The population in studies was most often males. 24 studies included only male participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations